Gratitude and Subjective Well‐Being in Older Chinese Adults in Nursing Homes: The Mediating Roles of Self‐Efficacy and Social Support - Chunqin Liu; Qing Luo; Liqin Song; Dongyi Luo; Huifang Chen; Xinyang Hu; Ying Zhou (Wiley, 2024)
ABSTRACT Aim With an aging global population, there has been a growing interest in the subjective well‐being (SWB) of older people. As a positive emotion, gratitude has been found to be significantly and positively associated with SWB. However, the mechanisms underlying the relationship between gratitude and SWB remain poorly understood. This study aimed to examine the mediating effects of social support and self‐efficacy in the relationship between gratitude and SWB among older Chinese adults in nursing homes. Design A cross‐sectional study. Methods A sample of 354 older adults in nursing homes aged 60 years and above was recruited across three nursing homes in Guangzhou, China. Participants completed the Gratitude Questionnaire‐Six‐Item Form, the World Health Organization's well‐being index, the General Self‐efficacy questionnaire and the Multidimensional Scale of Perceived Social Support. Structural equation modelling was used to evaluate the relationships between gratitude, self‐efficacy, social support and SWB. A bootstrap test was performed to test mediating roles of self‐efficacy and social support. Results Gratitude was found to be significantly and positively associated with SWB (β = 0.294, p < 0.001). Self‐efficacy and social support independently mediated the relationship between gratitude and SWB (indirect effect of self‐efficacy: Standardised β = 0.105, 95% CI [0.061, 0.157]; indirect effect of social support: Standardised β = 0.116, 95% CI [0.444, 0.191], all p < 0.001). Additionally, the results indicated that the mediating effect of self‐efficacy was not significantly different from that of social support in the link between gratitude with SWB. Conclusion These findings presented strong evidence that self‐efficacy and social support provided the underlying mechanisms through which gratitude was associated with SWB in Chinese nursing home residents. This highlighted the need to develop interventions aiming at increasing gratitude, self‐efficacy and social support to promote SWB among elderly people. Patient or Public Contribution No patient or public contribution.